2016
DOI: 10.1089/dna.2016.3251
|View full text |Cite
|
Sign up to set email alerts
|

A Ramie bZIP Transcription Factor BnbZIP2 Is Involved in Drought, Salt, and Heavy Metal Stress Response

Abstract: bZIP transcription factors play key roles in plant growth, development, and stress signaling. A bZIP gene BnbZIP2 (GenBank accession number: KP642148) was cloned from ramie. BnbZIP2 has a 1416 base pair open reading frame, encoding a 471 amino acid protein containing a characteristic bZIP domain and a leucine zipper. BnbZIP2 shares high sequence similarity with bZIP factors from other plants. The BnbZIP2 protein is localized to both nuclei and cytoplasm. Transcripts of BnbZIP2 were found in various tissues in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 39 publications
1
22
0
Order By: Relevance
“…Previously, studies showed that various bZIP genes were involved in regulating plant response to abiotic stresses such as salt, drought and low temperature, etc. [13,39]. Overexpression of TabZIP60 in wheat confers multiple abiotic stress tolerances [13], and overexpression of TaWRKY2 could increase drought tolerance of transgenic wheat [40].…”
Section: Discussionmentioning
confidence: 99%
“…Previously, studies showed that various bZIP genes were involved in regulating plant response to abiotic stresses such as salt, drought and low temperature, etc. [13,39]. Overexpression of TabZIP60 in wheat confers multiple abiotic stress tolerances [13], and overexpression of TaWRKY2 could increase drought tolerance of transgenic wheat [40].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, GhABF2 from cotton has been shown to facilitate drought and salt stress tolerance in transgenic cotton through an ABA-dependent pathway, as supported by higher antioxidant enzyme activities and proline content in transgenic plants under drought and salt stress [ 78 ]. In addition, functional analysis of grape ( Vitis vinifera ) VvbZIP23 [ 161 ], lotus root ( Nelumbo nucifera ) LrbZIP [ 162 ], T. hispida ThbZIP [ 163 ], and ramie ( Boehmeria nivea ) BnbZIP2 [ 79 ] genes demonstrated that all these bZIP TFs play critical roles in regulating salt stress along with other abiotic stresses.…”
Section: Transcription Factors Involved In Abiotic Stress Responsementioning
confidence: 99%
“…Under drought stress, the transgenic Arabidopsis plants of IbbZIP1 showed significant upregulation of the genes involved in ABA and proline biosynthesis and reactive oxygen species scavenging system, so as to significantly decrease of H 2 O 2 content (Kang et al, 2019). During seed germination and plant development, transgenic ramie plants overexpressing BnbZIP2 were more sensitive to drought stress than wild-type (Huang et al, 2016). In addition, overexpression of transcription factors such as Arabidopsis thaliana ABF3 (Wang Z. et al, 2016) and wheat TabZIP60 (Zhang L. N. et al, 2015) in plants can significantly improve the drought resistance of transgenic plants.…”
Section: Bzip Tfs Involved In Drought Stress Responsementioning
confidence: 99%